Intellectual Capital's Role in Enhancing Profitability During the Pandemic: A Comparative Study of Indonesia and Thailand - Elsinta, Laurentia Yuke; Marlina, Maria Asumpta Evi; Kohardinata, Cliff (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 2 (2024), 2024)
COVID-19 had a dual effect on Indonesian and Thai company sub-sectors, dampening profitability while accelerating digital transformation bolstered by intellectual capital (IC) metrics such as VACA, VAHU, STVA, and VAIC. This quantitative study employed purposive sampling across food and beverage, agriculture, electronics, chemical, and automotive sub-sectors, encompassing 55 IDX-listed and 63 SET-listed companies from 2020 to 2022, yielding 354 observations. Data underwent descriptive statistics, classical assumption tests, and multiple linear regression analysis. Results showed significant positive impacts of VACA, VAHU, STVA, and VAIC on profitability in both countries. However, Thailand's firms prioritized structural capital, contrasting with Indonesian firms emphasizing human and intellectual capital. Future research could extend to other developed Asian nations, diverse industries, and explore the MVAIC model to uncover IC's broader profitability impacts. Keywords : human capital, structural capital, earning before interest and tax, global crisis